Point-of-Care Ultrasound-Guided Management of Fulminant Influenza A(H3) with Staphylococcus aureus Necrotizing Pneumonia and Acute Cardiopulmonary Failure: A Case Report - Luigi Vetrugno; Giovanni Serena; Stefania Buttera; Pierpaolo Accolla; Davide Pecori; Irene Batticci; Davide Stolfo; Massimo Imazio; Igor Vendramin; Flavio Bassi (Healthcare, 2026)
Background: Seasonal influenza is typically a self-limiting illness in healthy young adults, but severe and potentially life-threatening complications can occur. Influenza A infection may predispose patients to secondary bacterial infections, including Staphylococcus aureus pneumonia and bacteremia, which can rapidly progress to necrotizing pneumonia, acute respiratory distress syndrome (ARDS), and cardiovascular dysfunction. Case Presentation: We report the case of a young adult with influenza A(H3) infection complicated by Staphylococcus aureus bacteremia, necrotizing pneumonia, ARDS, and biventricular dysfunction. The patient experienced rapid cardiopulmonary deterioration requiring advanced critical care support, including extracorporeal membrane oxygenation (ECMO) and left ventricular unloading. Serial point-of-care ultrasound (POCUS) was central to clinical management, enabling early recognition of worsening respiratory and cardiac function and guiding timely escalation of supportive strategies. Conclusions: This case highlights the potential severity of influenza-associated complications even in young and previously healthy individuals. Repeated POCUS assessment can play a pivotal role in detecting rapid cardiopulmonary deterioration and guiding advanced interventions. Efficient hub-and-spoke organization may further support timely referral and management of critically ill patients requiring ECMO and specialized care.